2016
DOI: 10.1002/pc.24072
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Graphene‐Based Rubber Nanocomposites

Abstract: Nowadays, rubber nanocomposites filled with graphene are endowed with promising future, because graphene has unique and outstanding mechanical, electrical, and thermal properties. This article summarizes the preparation and functionalization of graphene, and introduces the preparation, properties, and the latest achievement of graphene/rubber nanocomposites. Meanwhile it draws conclusions about factors that influence the properties of graphene‐based rubber composites. Finally, it gives the outlook and prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 100 publications
(116 reference statements)
0
29
0
Order By: Relevance
“…In order to achieve significant improvement of the polymer properties, nanoscale homogenous dispersion of graphene in the polymer matrix is essential [248]. Homogeneous dispersion minimizes the formation of concentrated local stresses and promotes uniform load transfer throughout the matrix [249][250][251]. However, achieving good dispersion is still a critical challenge, because graphene has a strong interaction between the layers due to the van der Waals force, and thus tend to agglomerate irreversibly or even to restack into graphite-like structures in the polymer matrix [196,252,253].…”
Section: Outlook Of Graphene/polymer Nanocompositesmentioning
confidence: 99%
“…In order to achieve significant improvement of the polymer properties, nanoscale homogenous dispersion of graphene in the polymer matrix is essential [248]. Homogeneous dispersion minimizes the formation of concentrated local stresses and promotes uniform load transfer throughout the matrix [249][250][251]. However, achieving good dispersion is still a critical challenge, because graphene has a strong interaction between the layers due to the van der Waals force, and thus tend to agglomerate irreversibly or even to restack into graphite-like structures in the polymer matrix [196,252,253].…”
Section: Outlook Of Graphene/polymer Nanocompositesmentioning
confidence: 99%
“…Scientists are working on carbon materials based on rubber composites due to the extraordinary properties of carbon‐based fillers . For instance, rubber composites filled with carbon black, rice bran carbon, bamboo charcoal, and graphene have been an increasing interest for improved mechanical, thermal, electrical, thermal conductivity as well as gas barrier properties of rubber. Considering the relatively low density, exceptional thermal, mechanical and electrical properties, carbon nanotubes (CNT) are the ideal candidates for the ultimate reinforcements in elastomer composites .…”
Section: Introductionmentioning
confidence: 99%
“…The application of CB in rubber composites has played an important role for more than one hundred years [19]. In recent years, CNTs and GE have aroused a great research interest in the field of rubber composites due to their functional properties as well as large specific surface area and high aspect ratio [20,21]. Previous studies found that CB, CNTs, and GE had a great impact on the mechanical properties, electrical and thermal conductivity, and fatigue properties of rubber composites, due to the different topological structure of fillers [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%